A new boat-like tungstoarsenate functionalized by carboxyethyltin and its catalytic properties. Issue 34 (21st March 2016) - Ji, Li-Ping; Du, Jing; Li, Jian-Sheng; Zhang, Lan-Cui; Sang, Xiao-Jing; Yang, He; Cui, Hong-Juan; Zhu, Zai-Ming
Abstract : The boat-like carboxyethyltin tungstoarsenate derivative was applied for the first time for oxidation catalysis and photocatalysis as well as for mimicking enzyme catalysis. Abstract : A new polyoxometalate (POM) estertin derivative, {C(NH2 )3 }Na10 K7 [(W4 O16 ){Sn(CH2 )2 COO}4 (B-α-AsW9 O33 )2 ]·25H2 O (1 ), has been synthesized from K14 [As2 W19 O67 (H2 O)]· n H2 O (As2 W19 ) and Cl3 SnCH2 CH2 COOCH3, which exhibits an unusual boat-like structural feature: four [Sn(CH2 )2 COO] 2+ groups surround a center W4 O16 cluster and link two [AsW9 O33 ] 9− subunits.1 shows efficient oxidation catalytic activity and can be applied for mimicking enzyme catalysis.